Root growth studies in bearing citrus trees and the field evaluation of clonally-propagated citrus rootstocks - Van Zyl, Abraham J.J.(Abraham Johannes Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric..) -- University of Stellenbosch, 1998.